2023
DOI: 10.51668/bp.8323300
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The parents' participation in adolescents' drug use treatment is a fundamental resource for good progress. Therefore, this pilot study demonstrates the feasibility of a brief intervention for drug-using adolescents, which contains sessions for parents and was adapted to a Brazilian sample. The protocol adaptation was tested in 28 adolescents (aged 14-18 years) to compare three conditions: 1) Group with adolescent/parent (GAP); 2) group with adolescent only (GA) and 3) treatment as usual (TAU). GAP post-test ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Cima, Smeets and Jelicic ( 25 ) found that non psychopathic aggressive men had high diurnal cortisol. Given that the perpetrators in the present study were found to engage mostly in reactive violence ( 26 ), it may be that the sample of perpetrators in this study were mostly non psychopathic as evidenced by the higher cortisol levels. In addition, previous studies have shown that type II or reactive perpetrators present a hyper-reactivity in anticipation of stress ( 27 ), so it could be that, in addition, the fact that they were interviewed at the department of probation, the stress associated with reminder of their being on probation produced a stress response and associated rise in cortisol.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Cima, Smeets and Jelicic ( 25 ) found that non psychopathic aggressive men had high diurnal cortisol. Given that the perpetrators in the present study were found to engage mostly in reactive violence ( 26 ), it may be that the sample of perpetrators in this study were mostly non psychopathic as evidenced by the higher cortisol levels. In addition, previous studies have shown that type II or reactive perpetrators present a hyper-reactivity in anticipation of stress ( 27 ), so it could be that, in addition, the fact that they were interviewed at the department of probation, the stress associated with reminder of their being on probation produced a stress response and associated rise in cortisol.…”
Section: Discussionmentioning
confidence: 79%
“…The increased testosterone places these men at risk for perpetrating violence as a result of testosterone’s influence on making more automatic judgements, biased by emotional factors due to a higher emotional sensitivity in conflictual situations ( 23 ). The increased cortisol following exposure to a stressor also suggests that perpetrators react more intensely to stress which further places them at risk for perpetration of violence and could explain the fact that the majority of the violence perpetrated is reactive ( 26 ).…”
Section: Summary Of Findingsmentioning
confidence: 99%